Clinical impact of 24-hour pH-metry in esophageal and stomach diseases diagnostics and pharmacological drugs efficacy testing - A. S. Trukhmanov; Olga A. Storonova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of the article. To present the technique of twentyfour hour esophageal and stomach pH-metry, indications and contraindications to the study, interpretation o intraesophageal and intragastric pH-metry parameters. Summary. Disorders of the stomach secretory function are one of the factors promoting development of many acid-related diseases such as gastric and duodenal erosions and ulcers, functional dyspepsia (epigastric pain syndrome), gastroesophageal reflux disease. Considering prevalence of these diseases and presence of severe complications, it is necessary to implement up-to-date diagnostic procedures in medical practice. Considerable diagnostic potential of pH-metry allow to verification of disease, individual estimation of the drug efficacy and treatment mode, control of response to carried out treatment, diagnostics of treatment resistance, detection of night «acid breakthrough» episodes and duodenogastric refluxes. Conclusion. 24-hour pH-metry is a fundamental diagnostic method for acid-related diseases. Measurement of gastric acidity and refluxate properties allows to individualize the carried-out therapy that is the most effective approach in treatment of patients.